The Relationship between Knowledge about Antibiotics with Usage Frequency of Non-prescription Antibiotics on Non-Medical Student of Sebelas Maret University - Nadya Kemala Amira; Arsita Eka Prasetyawati; Ratih Puspita Febrinasari (Nexus Kedokteran Komunitas, 2016)
Background: Antibiotics are the drugs most widely used and abused in the world. The most frequent form of antibiotic misuse is self-medication by various groups of society including students. Lacking of knowledge of the students, especially non-medical students, about antibiotics plays an important role in the discovery of many cases of antibiotics misuse. This study aimed to investigate the relationship between knowledge about antibiotics with usage frequency of non-prescription antibiotics on non-medical student of Sebelas Maret University. Method: This study was an observational analytic study with cross sectional approach. Sample collected from 186 non-medical students from 5 faculties in Sebelas Maret University which were randomly drawn by cluster random sampling technique. Each respondent was given a questionnaire regarding knowledge about antibiotics and the usage frequency of non-prescription antibiotics that has been tested for validity and reliability by researcher. The research data were tested with the nonparametric Spearman correlation test (? = 0.05). Result: Spearman correlation test results a significant correlation between knowledge about antibiotics with usage frequency of non-prescription antibiotics on non-medical students of Sebelas Maret University with p < 0.05 (p = 0.000). The test results also showed a strong correlation between the two variables with a correlation coefficient (r) -0.681, with increased knowledge about antibiotics will decrease the usage frequency of non-prescription antibiotics on non-medical students of Sebelas Maret University. Conclusion: There was a strong relationship between knowledge about antibiotics with the usage frequency of non-prescription antibiotics on non-medical students of Sebelas Maret University. Better knowledge of antibiotics, would reduce the usage frequency of non-prescription antibiotics. Keywords: antibiotics, knowledge about antibiotics, the usage frequency of non-prescription antibiotics